Using Selected Stories from Storycanada.ca Website: The Effect of Using Digital Children’s Literature on EFL College Students’ Vocabularies at UNP - Mulyati, Tri; Marlina, Leni (Universitas Negeri Padang, 2024)
Digital children’s literature is one of the media that can be used in learning as a way to improve EFL students vocabulary . The purpose of this study is to ascertain whether or not using the digital children’s literature help to improve the vocabulary at Universitas Negeri Padang . A collection of digital childrens literature stories from storybookscanada.comwas used in this experimental study .This study used quasi-experimental research and quntitative approach. The popuation was English languange education major students who enrolled in Introduction to Literature subject for the 2022/2023 academic year . The sample was two classes consisting 63 students from K3 and K7 which were selected using cluster random sampling . The information for the vocabulary test was acquired via pre-test and post-test of EFL college students’ vocabularies and consisting of 100 vocabularies taken from 14 selected stories on storybookscanada.com . A collection of 14 stories completed with vocabulary exercises and vocabulary list was used as the reading daily treatment within 14 days. Based on the results, the experimental class’s vocabulary before treatment was 339,57 or 67,92 % and students vocabulary after treatment was 379,42 or 75,88 % . Conversely, with regard to the control group , they did not experience much change in their pre-test and post-test results which were for vocabulary level from 356,97 or 71,39 % to 361,71 or 72,34 % . This research proves that employing digital children’s literature in the form of picture books on storybookscanada.comwith structural exercises has a significant effect on improving EFL college students’ vocabularies at UNP.